Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

LIDAR-based visibility map for plan position indicator (PPI) scans and range height indicator (RHI) scans – methodology and observations in two uncommon haze cases in Hong Kong - Man Lok Chong; Ping Cheung; Wai Ho Tang; Chun Kit Ho; Pak Wai Chan (Atmospheric Environment, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Dual-Aircraft Joint Observation of Cloud Microphysics in Typhoon Trami (2024) over the South China Sea - Shuai Zhang; Yufan Dai; Pak-Wai Chan; Ping Cheung; Jie Tang (Journal of Meteorological Research, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

Predicting Convectively Induced Turbulence With Regionally Convection-Permitting Simulations - Haoming Chen; Christy Yan-yu Leung; Ping Cheung; Haolin Liu; Sai Tick Chan; Xiaoming Shi (Asia-Pacific Journal of Atmospheric Sciences, 2025)
Convectively induced turbulence (CIT) is a severe aviation hazard. It is challenging to forecast CIT because low-resolution models cannot explicitly resolve convective motions at kilometer scales. In this study, we used the Model for Prediction Across Scales (MPAS) to simulate CIT cases with convection-permitting resolution ( $$\sim $$ ∼ 1 km) in the region of the CIT events and coarse resolution in other parts of the globe. We developed a method to estimate the eddy dissipation rate (EDR) using the resolved wind field of the MPAS simulations. The method is based on explicit filtering and reconstruction in the turbulence modeling for large-eddy simulations (LES). It estimates turbulence kinetic energy (TKE), which is then used to derive EDR. The new method produces different turbulence distribution and intensity than previous methods based on second-order structure functions and convective gravity wave drag, with higher accuracy and better correlation with observations for CIT cases tested in this study. The 1-km resolution simulation generates more accurate EDR and improves spatial patterns, but it is computationally demanding. The 3-km resolution can get benefits from reasonable accuracy and affordable computational cost. Because convection-permitting resolutions are in the gray zone for simulating convection, we evaluated the sensitivity of the prediction to the variations in physical and numerical schemes. Varying cumulus convection parameterization and monotonicity of numerical schemes are identified as practical approaches to generate beneficial ensemble spread. However, the physical perturbation-based ensemble has limitations, and initial condition perturbations are still necessary to encompass uncertainties in the development of convection.

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Proactive and Brief Smoking Cessation Intervention for Smokers at Outdoor Smoking “Hotspots” in Hong Kong - Sophia Siu Chee Chan; Yee Tak Derek Cheung; Zoe Wan; Man Ping Wang; Tai-hing Lam (Journal of Cancer Education, 2018)

Food wastes as fish feeds for polyculture of low-trophic-level fish: bioaccumulation and health risk assessments of heavy metals in the cultured fish - Zhang Cheng; Cheung-Lung Lam; Wing-Yin Mo; Xiang-Ping Nie; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Environmental mercury concentrations in cultured low-trophic-level fish using food waste-based diets - Zhang Cheng; Wing Yin Mo; Yu Bon Man; Cheung Lung Lam; Wai Ming Choi; Xiang Ping Nie; Yi Hui Liu; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

An overview of nowcasting development, applications, and services in the Hong Kong Observatory - Ping-Wah Li; Wai-Kin Wong; Ping Cheung; Hon-Yin Yeung (Journal of Meteorological Research, 2014)

Dietary exposure of Hong Kong secondary school students to total mercury and methylmercury from fish intake - Anna Shiu Ping Tang; Ka Ping Kwong; Stephen Wai Cheung Chung; Yuk Yin Ho; Ying Xiao (Food Additives & Contaminants Part B-Surveillance, 2009)

The chinchilla microdialysis model for the study of antibiotic distribution to middle ear fluid - Belinda W. Y. Cheung; Wei Liu; Ping Ji; Linda L. Cartier; Zhihong Li; Nael Mostafa; Ronald J. Sawchuk (The AAPS Journal, 2006)